THE ROLE OF OCULAR BLOOD FLOW IN THE PATHOGENESIS OF GLAUCOMA - Yulia Primitasari; Evelyn Komaratih (Jurnal Kedokteran Syiah Kuala, 2019)
Abstract. Glaucoma is currently the second leading cause of blindness worldwide and the prevalence is expected to increase. Despite lowering of IOP, vascular risk factors, genetics, and other systemic conditions could progress the glaucoma damage. Ocular blood flow has emerged as an increasingly prevalent glaucoma risk factor in large population-based trials. Abnormal  perfusion  and  the  subsequent  ischemia  of  the ONH  play  a  major  role  in  the  glaucomatous  damage. Ocular Blood flow is unstable if IOP fluctuates on a high enough or blood pressure on a low enough level to exceed temporarily the autoregulation capacity. IOP fluctuation is also related to both an increase in scotomas and an increase in diffuse visual fields damage.  OBF is unstable if autoregulation itself is disturbed. In  glaucoma  the  response  of  retinal  and  optic nerve head  blood flow to flicker  stimulation  is  reduced.  Primary  vascular  dysregulation appears  to  be  associated  with  abnormal  retinal  neurovascular  coupling,  because  vasospastic  subjects  show  a reduced  response  to  flicker  stimulation.Keywords: ocular blood flow, glaucoma